Water Supply and Sanitation in Mauritania : Turning Finance into Services for 2015 and Beyond - World Bank (Nairobi, 2014)
The situation within the water supply and sanitation (WSS) sector in Mauritania is somewhat contradictory: in spite of the weakness of the institutions in charge of the sector and the lack of financing for sanitation and, more recently, for the rural water supply (RWS) subsector, significant improvements have been made in the access rates since 1990. The institutional reform of the RWS subsector, notably marked by the implementation of a delegated management system for water supply networks, has led to improvements in both service quality and access, at a pace which remains only slightly below that required to meet the Millennium Development Goal (MDG) targets. In rural areas, the institutional framework remains poor and unstable. The management of water supply networks still needs to be improved; the sanitation subsector lacks both a clear intervention strategy and resources. These are the priority areas that need to be worked on to stimulate the capacity to mobilize and absorb financing, both domestic and donor. This second AMCOW Country Status Overview (CSO2) has been produced in collaboration with the Government of Mauritania and other stakeholders.